CONCEPTUAL STUDY ON THE EFFECT OF MOORVADI CHOORNAM IN POST CHEMOTHERAPY COMPLICATIONS (International Journal of Ayurveda and Pharma Research, 2021)
Cancer, a disease which has enormously multiplied over a last few decades, put to suffer tens of millions of people all over the world irrespective of gender, age or colour. The incidence of patients with cancer in India among males was 94.1 per 100,000 and among females 103.6 per 100,000 in the year 2020. 1 in 9 Indians develop cancer during their life time. Now days, the survival rate of cancer is much better due to vigorous interventions. Chemotherapy, is one of the main tool to kill the rapidly growing cancer cells. i.e., it shows its poisonous effect or simply they are poisons. The effect of chemo drugs on normal cells often causes many side effects. In fact the administration of chemo drugs results in the accumulation of poisons that shows symptoms like hair fall, mouth sores, fatigue, loss of appetite etc. Many complications develop after chemotherapy due to Dhatuagnimandya occurring as a result of the accumulation of Garavisha (artificial poison). Most of the complications noticed are similar to Garavisha lakshanas such as Pandu, Alpagni, Durbalatha etc. Acharya mentioned the yoga “Moorvadichoornam” with proper Anupana, which is specified for indigestion due to Garavisha consisting of drugs with many properties to compensate the side effect of chemotherapy. In this paper, a conceptual study is proposed to evaluate the effect of Moorvadi choornam in post chemotherapeutic complications. Signs of Agnimandya is very clear at the level of Dhatus and this drug combination is expected to act at Jadaragni and Dhatuagni level.